Urgensi Resolusi Konflik Klaim Nine Dash Line Tingkok Di Perairan Natuna Utara - Muhammad Wirtsa Firdaus; Andri Yanto; Faidatul Hikmah; Sigit Nugroho (Universitas Semarang, 2023)
The purpose of this study is to elaborate the urgency of resolving the Chinese and Indonesian Nine Dash Line conflict in North Natuna waters. As a strategic area with economic resource value and important global shipping lanes, the creation of a sense of security and legal certainty is an unavoidable necessity. The method used in the research is juridical-normative, with a review of laws and regulations, international legal norms, and international arbitration jurisprudence related to China's claims to the South China Sea and North Natuna. International jurisdiction based on UNCLOS 1982 establishes North Natuna as part of Indonesia's EEZ with sovereign rights. China's claims and direct intervention against North Natuna are illegal and violate the norms of international law. In this regard, differences in views and national interests between Indonesia and China result in a number of potential conflicts in North Natuna, including the entry of fishing boats and Chinese coastal patrols. In contrast to a number of related literature, this study specifically provides strategic considerations related to the most potential approach in conflict resolution, namely through ASEAN-China collective diplomacy with the Code of Conduct. Identification of conflict resolution strategies is a fundamental and urgent aspect in this study, with comprehensive consideration related to the causes, interests, and projects of conflict resolution that occurred in North Natuna. Tujuan penelitian ini adalah untuk mengelaborasi urgensitas penyelesaian konflik Nine Dash Line Tiongkok dan Indonesia di perairan Natuna Utara. Sebagai kawasan strategis dengan nilai sumberdaya ekonomi dan jalur perlintasan pelayaran global yang penting, penciptaan rasa aman dan kepastian hukum menjadi kebutuhan yang tidak dapat dihindari. Metode yang digunakan dalam penelitian adalah yuridis-normatif, dengan pengkajian terhadap peraturan perundang-undangan, norma hukum internasional, serta yurisprudensi arbitrase internasional terkait dengan klaim Tiongkok atas Laut Tiongkok Selatan dan Natuna Utara. Yurisdiksi internasional berdasarkan UNCLOS 1982 menetapkan Natuna Utara sebagai bagian ZEE Indonesia dengan hak berdaulat. Klaim dan intervensi langsung Tiongkok terhadap Natuna Utara adalah bentuk tindakan ilegal dan menyalahi norma hukum internasional. Dalam hal ini, perbedaan cara pandang dan kepentingan nasional antara Indonesia dan Tiongkok menghasilkan sejumlah potensi konflik di Natuna Utara, termasuk diantaranya dengan masuknya kapal nelayan dan patroli pantai Tiongkok. Berbeda dengan sejumlah literatur terkait, penelitian ini secara spesifik memberikan pertimbangan strategis terkait pendekatan yang paling potensial dalam resolusi konflik, yakni melalui diplomasi kolektif ASEAN-Tiongkok dengan Code of Conduct. Identifikasi strategi resolusi konflik merupakan aspek yang fundamental dan urgentif dalam penelitian ini, dengan pertimbangan komprehensif terkait dengan penyebab, kepentingan, dan proyekni penyelesaian konflik yang terjadi di Natuna Utara.